Sails of the Herring Fleet : Essays on Beckett. (University of Michigan Press, 2009)
Sails of the Herring Fleet traces esteemed director and theorist Herbert Blau's encounters with the work of Samuel Beckett. Blau directed Beckett's plays when they were still virtually unknown, and for more than four decades has remained one of the leading interpreters of his work. In addition to now-classic essays, the collection includes early program notes and two remarkable interviews -- one from Blau's experience directing Waiting for Godot at San Quentin prison, and one from his last visit with Beckett, just before the playwright's death. Herbert Blau is Byron W. and Alice L. Lockwood Professor of the Humanities, University of Washington.